A Case Study on the Adoption of Cloud Computing in Malaysia from The Perspectives of Cloud Providers - Puad, Noor Hazwani Mohamad (International Journal of Innovation in Enterprise System, 2019)
The objective of this study is to discover the perspectives of cloud providers towards cloud computing adoption in Malaysia in terms of the challenges faced by cloud providers and reasons for the adoption. Data were collected through semi structured interviews with three cloud providers. The findings indicated security concern, difficulties in learning cloud computing infrastructure, changes in IT roles, high cost of bandwidth and life span of IT equipment as challenges faced by cloud providers in providing cloud service in Malaysia. This study also discovered cloud scalability, end-to-end management, high level security, and customizable as the reasons on cloud computing adoption. The findings of this study help people to understand more about the current situation of cloud computing adoption in Malaysia